Gestational Diabetes Mellitus and Obesity are Related to Persistent Hyperglycemia in the Postpartum Period - Rehder, Patricia Moretti; Borovac-Pinheiro, Anderson; de Araujo, Raquel Oliveira Mena Barreto; Diniz, Juliana Alves Pereira Matiuck; Ferreira, Nathalia Lonardoni Crozatti; Branco, Ana Claudia Rolim; Dias, Aline de Fatima; Pereira, Belmiro Gonçalves (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2021)
Objective To evaluate the obstetric and sociodemographic characteristics of gestational diabetic women who maintained hyperglycemia in the postpartum period (6–12 weeks postpartum).Methods This is a longitudinal cohort study with women who have had gestational diabetes and/or macrosomic children between March 1st, 2016 and March 1st, 2017. Between 6 and 12 weeks after birth, women who had gestational diabetes collected fasting glycemia, glucose tolerance test, and glycated hemoglobin results. The data were collected from medical records and during an interview in the first postpartum consultation. A statistical analysis was performed using frequency, percentage, Chi-Squared test, Fisher exact test, Mann-Whitney test, and multivariate Poisson regression. The significance level adopted for the statistical tests was 5%.Results One hundred and twenty-two women were included. Most of the women were younger than 35 years old (70.5%), white, multiparous, and with no history of gestational diabetes. Thirteen percent of the participants developed persistent hyperglycemia. A univariate analysis showed that maternal age above 35 years, being overweight, having grade 1 obesity and weight gain under 5 kg was related to the persistence of hyperglycemia in the postpartum period.Conclusion Maternal age above 35 years, obesity and overweight, and the diagnosis of gestational diabetes in the first trimester of pregnancy are associated with hyperglycemia during the postpartum period.
Keywords: gestational diabetes; obesity; hyperglycemia; postpartum period; overweight